Test of Cure Return Rate and Test Positivity, Strengthening the US Response to Resistant Gonorrhea, United States, 2018–2019. Issue 12 (December 2021) - Schlanger, Karen; Mauk, Kerry; Learner, Emily R.; Schillinger, Julia A.; Nishiyama, Masayo; Kohn, Robert; Thibault, Christina; Hermus, Helen; Dewater, Joey; Pabon, Vonda; Black, Jamie; St. Cyr, Sancta; et al.
Abstract : Background: Reduced antibiotic susceptibility (RS) in Neisseria gonorrhoeae (GC) may increase treatment failure. Conducting tests of cure (TOC) for patients with RS-GC may facilitate identification of treatment failures. Methods: We examined 2018 to 2019 data from 8 jurisdictions participating in the US Centers for Disease Control and Prevention's Strengthening US Response to Resistant Gonorrhea project. Jurisdictions collected GC isolates and epidemiological data from patients and performed antimicrobial susceptibility testing. Minimum inhibitory concentrations of ceftriaxone, 0.125 μg/mL or greater; cefixime, 0.250 μg/mL or greater; or azithromycin, 2.0 μg/mL or greater were defined as RS. Patients with RS infections were asked to return for a TOC 8 to 10 days posttreatment. We calculated a weighted TOC return rate and described time to TOC and suspected reasons for any positive TOC results. Results: Overall, 1165 patients were diagnosed with RS infections. Over half returned for TOC (weighted TOC, 61%; 95% confidence interval, 50.1%–72.6%; range by jurisdiction, 32%–80%). Test of cure rates were higher among asymptomatic (68%) than symptomatic patients (53%, P = 0.001), and men who have sex with men (62%) compared with men who have sex with women (50%; P < 0.001). Median time between treatment and TOC was 12 days (interquartile range, 9–16). Of the 31 (4.5%) TOC patients with positive results, 13 (42%) were suspected because of reinfection and 11 (36%) because of false-positive results. There were no treatment failures suspected to be due to RS-GC. Conclusions: Most patients with a RS infection returned for a TOC, though return rates varied by jurisdiction and patient characteristics. Test of cure can identify and facilitate treatment of reinfections, but false-positive TOC results may complicate interpretation and clinical management. Abstract : Most (61%) patients with a reduced antibiotic susceptible gonococcal infection returned for a test of cure to facilitate detection of possible treatment failures. Tests of cure also detected occasional reinfections and false-positive results.Supplemental digital content is available in the text.